Hubungan Persepsi Siswa tentang Kompetensi Pedagogik Guru dengan Hasil Belajar Geografi Siswa Kelas XI di MAN 2 Kota Padang Panjang - Fajriyani, Yulia; Anwar, Syafri (Lembaga Yasin AlSys, 2024)
This research aims to find out the extent of the relationship between student’s perceptions of teachers’ pedagogical competence and the geography learning outcomes of class XI IPS students at MAN 2 Padang Panjang City. This type of research includes quantitative correlational research. The population in this study was class XI IPS Students in Man 2 Padang Panjang City for the 2023/2024 academic year, totaling 89 students. The sampling teachnique used was proportional random sampling with a proportion of 10% and a sample of 67 students was obtained. Data analysis uses descriptive data tests, analytical requirements tests with calculations using Exel and SPSS 23.0 formulas.